2022
DOI: 10.1002/smll.202203886
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐Up Templated and Oriented Crystallization for Inverted Triple‐Cation Perovskite Solar Cells with Stabilized Nickel‐Oxide Interface

Abstract: Inverted‐structure perovskite solar cells (PSCs) are known for their superior device stability. However, based on nickel‐oxide (NiOx) substrate, disordered crystallization and bottom interface instability of perovskite film are still the main factors that compromise the power conversion efficiency (PCE) of PSCs. Here, 2D perovskite of thiomorpholine 1,1‐dioxide lead iodide (Td2PbI4) is introduced as a template to prepare 3D perovskite thin film with high crystal orientation and large grain size via a bottom‐up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…As described in the previous reports, Ni 3+ acceptors generate p-type conductivity in the NiO x thin film. ,, The film’s conductivity was measured using J-V measurements (Figure S8a). As shown in Table S1, the NiO x -NaOH and NiO x -KOH films display higher conductivity; the latter is the best.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As described in the previous reports, Ni 3+ acceptors generate p-type conductivity in the NiO x thin film. ,, The film’s conductivity was measured using J-V measurements (Figure S8a). As shown in Table S1, the NiO x -NaOH and NiO x -KOH films display higher conductivity; the latter is the best.…”
Section: Resultsmentioning
confidence: 90%
“…The intercept of the linear regime with the x -axis of the Mott–Schottky plot represents the built-in potential ( V bi ). It is observed that the NiO x -KOH device shows a higher V bi (0.96 V) than that of NiO x -NaOH (0.84 V), which was favorable for interfacial charge separation and extraction. , …”
Section: Resultsmentioning
confidence: 96%
“…The organic spacer cation of thiomorpholine 1,1-dioxide hydrochloride (TdCl) has a stronger interaction with PbI 2 compared with FAI, thus making it easier to generate Td 2 PbI 4 2D microcrystals when introduced into the perovskite precursor solution. 125 This is veried by the additional diffraction peaks in XRD and the Stokes shi between lm absorption and emission peaks. As depicted in Fig.…”
Section: Passivation Strategies At Buried Interface Through 2d Perovs...mentioning
confidence: 98%
“…In particular, the D/P treatment triggered a 12 nm blue shift of emission peak (from 981 nm for D/S-treated perovskite to 969 nm for D/P-treated perovskite). [39,40] These data mean that the carrier nonradiative recombination was significantly reduced and the defects were well eliminated by DMPU treatment. Then, the time-resolved photoluminescence (TRPL) spectra were also applied to investigate the carrier lifetime inside these films, as shown in Figure S8 (Supporting Information).…”
Section: Film Quality Fabricated With Different Solventsmentioning
confidence: 99%